Pengaruh Model Pembelajaran Course Review Horay Berbantuan Media Video Animasi Powtoon Terhadap Hasil Belajar IPAS Siswa Kelas IV SD Inpres 1 Tanamodindi - Nur Kamilah; Zulnuraini Zulnuraini; Herlina Herlina; Sisriawan Lapasere (JURNAL DIKDAS, 2025)
This research aims to determine the effect of the Course Review Horay (CRH) learning model, assisted by Powtoon-based animation video media, on the IPAS learning outcomes of Grade IV students at SD Inpres 1 Tanamodindi. The population in this study consists of all grade IV students at SD Inpres 1 Tanamodindi for the 2024/2025 academic year, totaling 47 students. The sample in this research comprised Grade IV-A as the experimental group and Grade IV-B as the control group. Data collection techniques used tests and documentation. The instrument used was a multiple-choice test instrument that had been tested for validity and reliability. Data analysis employed prerequisite tests, including normality and homogeneity tests, as well as hypothesis testing using the Independent Sample t-test, which was analyzed using SPSS version 25. Based on the analysis results of the Independent Sample t-test, a significant value (Sig. 2-tailed) of 0.000 < 0.05 was obtained from the pretest and posttest of the experimental group, so H0 is rejected, and H1 is accepted.